"Aula de religião, pra quê?": papel do ensino religioso em duas escolas de Boa Vista - RR : um estudo de caso - Viana, Maria Lúcia Silva (2015)
This paper consists on a case study as taught, between 2014 and 2015, in two schools from the city of Boa Vista, Roraima - one from the state education system, and the other from the private one - seeking to offer enough data for formulating a balanced response to a question from students, parents and teachers: "religion education, what for?". The starting point was the observation that including Religious Education in the official curriculum does not always bring the expected results. But since that inclusion was allowed by the Brazilian Constitution and the Law of Directives and Bases of National Education, how can the state guarantee that the curricula ensures the respect for diversity of creeds and how to restrain proselytizing? Given the risks, does it make sense to offer the discipline in the state education system? We aimed then to understand the methodological procedures and teaching resources used by teachers of religious education in the studied groups, analyzing the different proposals of religious education, identifying similarities and differences between the teaching approaches of the public and private systems of education and trying to offer elements for an improvement of the Religious Education and the implementation of mechanisms to minimize the risks of prejudice and proselytizing.